PHYLOGENETIC AFFINITIES of "CHANTRANSIA" STAGES IN MEMBERS of THE BATRACHOSPERMALES and THOREALES (RHODOPHYTA) - Necchi, Orlando [UNESP]; Oliveira, Mariana Cabral (Wiley-Blackwell, 2011)
This study evaluated the phylogenetic relationship among samples of "Chantransia" stage of the Batrachospermales and Thoreales from several regions of the world based on sequences of two genes-the plastid-encoded RUBISCO LSU gene (rbcL) and the nuclear SSU ribosomal DNA gene (SSU rDNA). All sequences of "Chantransia macrospora" were shown to belong to Batrachospermum macrosporum based on both molecular markers, confirming evidence from previous studies. In contrast, nine species are now associated with "Chantransia pygmaea," including seven species of the Batrachospermales and two of the Thoreales. Therefore, the presence of "C. macrospora" in a stream can be considered reliable evidence that it belongs to B. macrosporum, whereas the occurrence of "C. pygmaea" does not allow the recognition of any particular species, since it is associated with at least nine species. Affinities of "Chantransia" stages to particular taxa were congruent for 70.5% of the samples comparing the rbcL and SSU analyses, which were associated with the same or closely related species for both markers. Sequence divergences have been reported in the "Chantransia" stage in comparison to the respective gametophyte, and this matter deserves further attention.
Keywords: Batrachospermales; Chantransia stage; freshwater Rhodophyta; rbcL; SSU rDNA; Thoreales